Disciplining Knowledge in Music Theory: Abstraction and the Recovery of Dialectics - Karl D. Braunschweig (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2012)
A critical rethinking of disciplinary tendencies in music theory reveals several important historical moments when the process of abstraction has reshaped aspects of tonal theory in profound ways, notably in the areas of counterpoint, harmony, and form. These moments of abstraction prioritize one musical feature over others, and frequently involve a discursive process of dissociation to solidify the legitimacy of the abstraction and resolve lingering logical contradictions. This often leads to a theoretical and historical distancing from the contexts in which certain practices emerged, and risks severing aesthetic connections between technique and meaning. The resulting imbalance in one or more of three dialectical pairs has additional disciplinary consequences, and invites renewed interest in three theoretical perspectives that can recognize changing musical concepts and at the same time recover some of the latent meanings buried in tonal music. These perspectives have received some attention in recent music analysis; in this article I wish to call attention to their deeper disciplinary role in compensating theoretical abstraction and dialectically mapping our theoretical field.